High-resolution x-ray diffraction of epitaxial bismuth chalcogenide topological insulator layers. (2nd February 2017) - Holý, V; Kriegner, D; Steiner, H; Stangl, J; Bauer, G; Springholz, G
Abstract: Stoichiometry and lattice structure of epitaxial layers of topological insulators Bi2 Te3 and Bi2 Se3 grown by molecular-beam epitaxy is studied by high-resolution x-ray diffraction. We show that the stoichiometry of Bi2 X3 – δ (X  =  Te, Se) epitaxial layers depends on the additional flux of the chalcogens Te or Se during growth. If no excess flux is employed, the resulting structure is very close to Bi1 X1 ( δ   =  1), whereas with a high excess flux the stoichiometric Bi2 X3 phase is obtained. From the x-ray data we determined the lattice parameters of the layers and their dependence on composition δ, as well as the degree of crystal quality of the layers.